Stress treatment: The effectiveness between guided and non-guided virtual reality setup - Zainudin A.R.R.; Yusof A.M.; Rusli M.E.; Yusof M.Z.M.; Mahalil I. (Institute of Electrical and Electronics Engineers Inc., 2023)
Stresses; emotions; guided and non-guided; Random users; Virtual navigation; Virtual reality